Coapproximation of functions convex on a disk by algebraic polynomials - Budnik, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
An estimate is obtained for the approximation of convex functions of two variables with bounded second derivatives on a disk by convex algebraic polynomials.